My First 5 Minutes Fairy Tales : The Pied Piper of Hamelin - Om Books international (Bharat Om Books International, 2019)
The town of Hamelin is plagued by rats. Can the mysterious Pied Piper get rid of all the rats in Hamelin? This is a beautiful retelling of the classic children fairy tale - The Pied Piper of Hamelin. With vibrant, captivating illustrations and simple text, it will spark the childs imagination, develop speech & language skills and encourage to read books.
Keywords: Traditional Literature - FairyTales -- Traditional Literature - FairyTales